Microeconomic Surplus in Health Care: Applied Economic Theory in Health Care in Four European Countries - Walzer, Stefan; Nuijten, Mark; Wiesner, Christof; Kaier, Klaus; Johansson, Per-Olov; Oertel, Stephan (Frontiers in Pharmacology, 2013)
Introduction: In economic theory economic surplus refers to two related quantities: Consumer and producer surplus. Applying this theory to health care “convenience” could be one way how consumer benefits might manifest itself. Methods: Various areas of economic surplus were identified and subsequently screened and analysed in Germany, Spain, The Netherlands and the UK: Caesarean births, emergency room visits (nights or weekends), drug availability after test results, and response surplus. A targeted literature search was being conducted to identify the associated costs. Finally the economic surplus (convenience value) was calculated. Results: The economic surplus for different health care areas was being calculated. The highest economic surplus was obtained for the example of response surplus IVF-treatments in The Netherlands. Conclusions: The analyzed examples in this article support the underlying hypothesis for this research: “Value of convenience defined as the consumer surplus in health care can be shown in different health care settings”. Again, this hypothesis should be accepted as a starting point in this research area and hence further primary research is strongly recommended in order to fully proof this concept.